Behind the green doors: What management practices lead to sustainable innovation - Mohd Zahari, Fadhilah; T., Ramayah (2012)
The notion of being green and competitive has gained substantial attention from both scholars and industry practitioners for the past few decades.It has been widely accepted that sustainable innovation (S1) is one approach that firms could adopt in becoming greener and yet competitive.Despite of this obsession, we know little of what firms are doing, or their practices that lead S1 to take place in their organizations.This paper reviews some of management practices, pertaining to technology, human resources and external relationship practices that are significantly influential to SI.The insights forwarded by this paper could provide some basis for future studies in this domain, particularly regarding the role of top management; as well as the guidelines for practitioners to realize environmental transformation in their organization.